C19orf66 is an interferon-induced inhibitor of HCV replication that restricts formation of the viral replication organelle - Kinast, Volker; Plociennikowska, Agnieszka; Anggakusuma; Bracht, Thilo; Todt, Daniel; Brown, Richard J. P.; Boldanova, Tujana; Zhang, Yudi; Brüggemann, Yannick; Friesland, Martina; Engelmann, Michael; Vieyres, Gabrielle; et al. (Journal of hepatology, 2020)
Background & Aims - HCV is a positive-strand RNA virus that primarily infects human hepatocytes. Recent studies have reported that C19orf66 is expressed as an interferon (IFN)-stimulated gene; however, the intrinsic regulation of this gene within the liver as well as its antiviral effects against HCV remain elusive. - Methods - Expression of C19orf66 was quantified in both liver biopsies and primary human hepatocytes, with or without HCV infection. Mechanistic studies of the potent anti-HCV phenotype mediated by C19orf66 were conducted using state-of-the-art virological, biochemical and genetic approaches, as well as correlative light and electron microscopy and transcriptome and proteome analysis. - Results - Upregulation of C19orf66 mRNA was observed in both primary human hepatocytes upon HCV infection and in the livers of patients with chronic hepatitis C (CHC). In addition, pegIFNα/ribavirin therapy induced C19orf66 expression in patients with CHC. Transcriptomic profiling and whole cell proteomics of hepatoma cells ectopically expressing C19orf66 revealed no induction of other antiviral genes. Expression of C19orf66 restricted HCV infection, whereas CRIPSPR/Cas9 mediated knockout of C19orf66 attenuated IFN-mediated suppression of HCV replication. Co-immunoprecipitation followed by mass spectrometry identified a stress granule protein-dominated interactome of C19orf66. Studies with subgenomic HCV replicons and an expression system revealed that C19orf66 expression impairs HCV-induced elevation of phosphatidylinositol-4-phosphate, alters the morphology of the viral replication organelle (termed the membranous web) and thereby targets viral RNA replication. - Conclusion - C19orf66 is an IFN-stimulated gene, which is upregulated in hepatocytes within the first hours post IFN treatment or HCV infection in vivo. The encoded protein possesses specific antiviral activity against HCV and targets the formation of the membranous web. Our study identifies C19orf66 as an IFN-inducible restriction factor with a novel antiviral mechanism that specifically targets HCV replication. - Lay summary - Interferon-stimulated genes are thought to be important to for antiviral immune responses to HCV. Herein, we analysed C19orf66, an interferon-stimulated gene, which appears to inhibit HCV replication. It prevents the HCV-induced elevation of phosphatidylinositol-4-phosphate and alters the morphology of HCV's replication organelle.
Gesehen am 29.09.2020